Characterization of blood donors with high haemoglobin concentration. Issue 2 (15th August 2012) - Magnussen, K.; Hasselbalch, H. C.; Ullum, H.; Bjerrum, O. W.
<x xml:space="preserve">Abstract</x> Background and Objectives The literature contains little on the prevalence and causes of high predonation haemoglobin levels among blood donors. This study aimed to characterize and develop an algorithm to manage would‐be donors with polycythaemia. Materials and Methods Between November 2009 and November 2011, we offered haematology consultations to blood donors with repeated haemoglobin concentration (Hb) above the WHO limit for polycythaemia vera (PV) (10·2 and 11·5 mm/16·5 and 18·5 g/dl for women and men, respectively). Investigation of such donors included Hb, haematocrit, mean cell volume, erythropoietin, ferritin, platelet count and leucocyte count, JAK2 V617 and JAK2 exon12 analysis, as well as other routine measurements. Results Among 46 such donors, 39 had a history of smoking, which contributes to erythrocytosis. Two had PV, five had severe hypertension, one of them because of renal artery stenosis, and two had diabetes mellitus. Thus, we found a high morbidity among such donors. Of the 36 others, 30 donated again before May 2012, at which time the Hb was significantly lower. Conclusion We recommend JAK2 V617 and JAK2 exon12 screening and clinical investigation for donors with concurrently high Hb, high haematocrit and iron deficiency. We also recommend that they stop or cut down on smoking to reduce the risk of thrombosis in general. We disqualified 10 of the donors.